Predatory insects in collapsing foci of bark beetles in Sumy region - Meshkova, V. L.; Vorobei, A. D.; Omelich, A. R. (Forestry and Forest Melioration, 2021)
Introduction The outbreaks of the bark beetles Ips acuminatus (Gyllenhal, 1827) and Ips sexdentatus (Boerner, 1767) (Coleoptera: Curculionidae: Scolytinae) have begun to collapse, while the prevalence of Tomicus piniperda (Linnaeus, 1758) and Tomicus minor (Hartig, 1834) is beginning to increase. Given that most predatory beetles attack different species of bark beetles, it is still important to study the occurrence of such predators in forest stands and to rear these entomophages for forest protection. Since predators consume bark beetles at different stages during rearing, it is also advisable to recognize the features of bark beetles spread in collapsing foci to determine the optimal places and time for their collection. The aim of the research was to evaluate the occurrence of bark beetles (Coleoptera: Scolytinae) and their predators in collapsing foci depending on certain stand characteristics. Materials and Methods The study was carried out in collapsing foci of bark beetles in Scots pine (Pinus sylvestris L.) stands in Sumy region. Sample trees of the 5th and 6th categories of health condition were analysed at 30 sample plots in three state forest enterprises of Polissya part of Sumy region and in seven state forest enterprises of the Forest-Steppe part of Sumy region (9 and 21 forestries respectively). Insects were counted on 25 ? 25 cm pallets from mid-May to mid-August 2021. Predatory insects were collected from each pallet to individual Eppendorf tubes, labeled, and later identified in the laboratory. Results and Conclusions The six predator Coleoptera species were found in the declining stage of outbreak cycle of bark beetles Ips acuminatus (Gyllenhal, 1827) and Ips sexdentatus (Boerner, 1767), namely Aulonium ruficorne (Olivier, 1790) (Colydiidae), Platysoma elongatum (Leach, 1817) (Histeridae), Rhizophagus depressus (Fabricius, 1792) (Monotomidae), Corticeus pini (Panzer, 1799) (Tenebrionidae), Thanasimus formicarius (Linnaeus 1758), and Thanasimus femoralis (Zetterstedt, 1828) (Cleridae). Platysoma elongatum and Aulonium ruficorne had the highest frequency of occurrence in the second decade of May, Thanasimus formicarius in the 3rd decade of May, Corticeus pini in the 1st decade of June, Rhizophagus depressus, Platysoma elongatum, and Aulonium ruficorne in the 3rd decade of June. The fragments of the stem with bark beetles for predators’ rearing have to be collected from the trees of the 5th category of health condition. It is necessary to collect Thanasimus formicarius for rearing in the 3rd decade of May and in the 1st decade of August, and Rhizophagus depressus, Platysoma elongatum, and Aulonium ruficorne – in the 3rd decade of June.